Material removal profile model simulations and experiments on the non-contact shear thickening polishing of K9 glass - Zhao, Jun; Wang, Wenbing; Qiu, Xianwei; Wang, Zixuan; Fan, Cheng (Journal of manufacturing processes, 2025)
To achieve the precise prediction and control of material removal profiles and workpiece surface shapes during shear thickening polishing, this paper introduces the non-contact shear thickening polishing (NCSTP) method. This method comprehensively considers processing parameters such as tool movement angle, tool rotation, machining gap, and flow field characteristics based on the NCSTP process. A theoretical model framework for NCSTP material removal profiles is established that integrates shear thickening fluid simulation and microscopic abrasive material removal mechanisms. This framework enables the accurate prediction of material removal profiles during both fixed-point machining and precession processing along a straight line, thereby revealing the NCSTP material removal mechanism. Experimental results from polishing optical K9 glass demonstrate highly consistent material removal profiles between the experimental and theoretical outcomes, with a maximum average error of 4.45 %. Furthermore, verification of the NCSTP model through linear precession polishing experiments on K9 optical glass show significant surface roughness improvement. Specifically, the surface roughness Ra decreases from 465.77 nm to 41.55 nm after single-feed polishing, resulting in a surface roughness improvement rate of 91.1 %. Additionally, numerical simulations of the NCSTP process reveal intermediate process parameters that are challenging to obtain directly through experiments, including the distributions of hydrodynamic pressure, shear stress, and abrasive particle velocity within the polishing fluid. These insights quantitatively elucidate the influence on the polishing material removal profile, thereby enhancing understanding of the material removal mechanism during NCSTP. [Display omitted] •An NCSTP method is proposed to achieve ultra-precision polishing of K9 optical glass.•Establish a material removal profile model based on shear thickening and microscopic abrasive material removal mechanism.•Numerical simulation reveals the influence of polishing parameters on the material removal profile.•The maximum average error between the theoretical material removal profile and the actual profile is 4.45%.